Improvement of Microsurgical Techniques in Orthotopic Rat Liver Transplantation - Veeravorn Ariyakhagorn (2018)
Background: Because of the limited tolerance to portal venous clamping, the model of liver transplantation in rats represents a difficult task, which requires a great proportion of experience. Since techniques that include the introduction of an artificial stent increase the risk of thrombosis, it was our goal to modify the classical vascular hand-sewn venous anastomosis technique by using a modified end-to-end knotless procedure. Materials and methods: Seventy-two animals were randomly assigned to 1 of 2 experimental groups, which differed by the technique for the 3 venous anastomoses (supra- and infrahepatic vena cava, portal vein). Group 1 comprised the established suturing technique for rat liver transplantation, whereas all venous anastomosis of the second group were performed using our modified technique. Results: With our method, average anhepatic time could be significantly reduced from 14 min 10 s (±100 s) to 11 min 40 s (±60 s) (P < 0.001). Kaplan-Meier survival rates demonstrated a better 7-d survival for the knotless (94%) compared to the classic technique (83%) (not significant, P = 0.137). Biliary complications were low in both groups but tended to be higher in the classical group. Conclusions: Our modified knotless anastomosis proves to be equally safe in regard to complications, improves timing, and provides excellent results in the model of orthotopic rat liver transplantation. © 2009 Elsevier Inc. All rights reserved.